Early Signs of End-Organ Damage in Retinal Arterioles in Patients with Type 2 Diabetes Compared to Hypertensive Patients - Jumar, Agnes; Ott, Christian; Kistner, Iris; Friedrich, Stefanie; Michelson, Georg; Harazny, Joanna M.; Schmieder, Roland (Microcirculation, 2016)
Eutrophic and hypertrophic remodeling are major vascular hallmarks for hypertension and diabetes-associated microvascular end-organ damage in peripheral arterioles. The aim of this study is to compare retinal arterioles of diabetic, hypertensive, and healthy individuals.Retinal parameters were assessed in 99 patients with T2DM, 158 hypertensive, and 149 healthy individuals. WT and CA of retinal arterioles (80-140 ?m) were measured noninvasively and in vivo by scanning laser Doppler flowmetry (Heidelberg Engineering, Germany).After adjustment for values differing between the groups (age, BMI, gender, HDL cholesterol and serum creatinine, systolic office BP), patients with T2DM showed no significant difference in WT (14.2 ± 3), and CA (4199 ± 1107) in comparison with hypertensive patients (WT = 13.3 ± 4, p = 0.18, CA = 3862 ± 1546, p = 0.10) and healthy individuals (WT = 13.1 ± 3, p = 0.55, CA = 3864 ± 1216, p = 0.86). However, the subgroup of patients with diabetes duration of more than 60 months showed greater WT (14.9 ± 4, p = 0.04) and CA (4557 ± 1137, p = 0.02) than the hypertensive group and greater WT (p = 0.04) and CA (p = 0.03) than the healthy group, which is consistent with hypertrophic remodeling.In the early stage of T2DM no hypertrophic remodeling was seen in retinal arterioles. However, hypertrophic remodeling was found in diabetic patients with more than 60 months duration of disease.
EVALuna2:3870